International Trade: Economic Growth Supports Export and Import Activities - Primadi Candra Susanto; Mochammad Subagio; Gratia Atanka Barus; Wenny Desty Febrian; Indra Sani (Greenation Research & Yayasan Global Resarch National, 2024)
The article International Trade: Supporting Economic Growth in Export and Import Activities is a scientific literature review article within the scope of strategic management science. This article aims to create a hypothesis regarding the relationship between factors, which can then be used for further research in the field of strategic management. Descriptive qualitative research methodology was used in this research. The data used in this research comes from previous research which is still relevant to the current investigation. Data was collected from leading academic online platforms, including Publish or Perish, Google Scholar, digital reference books, and Sprott journals. The findings of this research are as follows: 1) Export activities in supporting economic growth play a role in international trade, and 2) Import activities to support economic growth play a role in international trade.